2020
DOI: 10.1021/acs.inorgchem.0c01760
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Magnetic 2D Co@NC-600 Material by Designing a MOF Precursor for Efficient Catalytic Reduction of Water Pollutants

Abstract: 2D metal–organic framework (MOFs) can be ideal sacrificial templates for fabricating nanomaterials because of active sites exposed on the surface rather than in pores and channels, often exhibiting improved performance in catalysis applications. In this study, the novel 2D layered cobalt-based MOF [Co­(TPT)­(fma)­(H2O)2]·3H2O (Co-MOF) has been constructed by the selection of high N atom content ligands. On this basis, a 2D nitrogen-doped carbon-coated cobalt nanoparticle composite (Co@NC) was prepared by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…High-resolution TEM confirmed the composite structure for the 2D Co/N-C hybrid. Simultaneously, the lattice fringe with an interplanar distance of ∼0.205 nm was assigned to the (111) crystal planes of Co. This confirmed the formation of zerovalent Co nanoparticles and the uniform distribution on the nitrogen-doped carbon matrix.…”
Section: Synthesis Of Mixedsupporting
confidence: 56%
“…High-resolution TEM confirmed the composite structure for the 2D Co/N-C hybrid. Simultaneously, the lattice fringe with an interplanar distance of ∼0.205 nm was assigned to the (111) crystal planes of Co. This confirmed the formation of zerovalent Co nanoparticles and the uniform distribution on the nitrogen-doped carbon matrix.…”
Section: Synthesis Of Mixedsupporting
confidence: 56%
“…Co@NC-600 0.5 0.1 2 100 2.5 [35] Co@N-CNT 0.25 1 5 100 0.05 [36] CoO x /CN-500 8 2 10 95 0.38 [37] Zn0.3Co2.7@NC 0.3 0.06 5 100 1.0 [38] Co-USi-800 0.36 0.4 4 98 0.22 [39] Co@INC 0.21 0.06 2 100 1.75 [28] Cu/Co@NCF 0.3 0.05 4 100 1.5 [40] Co@NCNT-11-800 2 3 12 94 0.05 [41] a…”
Section: This Workmentioning
confidence: 99%
“…MV/RhB UV light 73.3/55.1 CNNSs/MIL-100(Fe) [109] RhB Visible light + H 2 O 2 100 N-Cu 2 O/carbon composites [110] MO Visible light 90 [{Co(5NH 2 -IPA)(1,2-bpe)}] 1 [111] RhB/MB Visible light + H 2 O 2 98/96 [Co 2 (1,4-BDC)(NCP) 2 ] [112] MV UV light 33.29 [Co 2 (4,4'-Hcpmb)(1,3-bib)] [113] MV UV light 94.7 [Co(bpco) 0.5 (tib)(H 2 O) 2 ] [114] MV UV light 55 [Mn 2 (μ 2 -H 2 O)(H 2 L)(CH 3 CN) 2 ] [115] MV UV light 51.73 [Mn(L) 0.5 (phen) • 0.5H 2 O] [115] MV UV light 55.31 MOF-5/LTH [116] MB UV-visible light 98.1 [Zn(L)(4,4'-bipy) • CH 3 CN] n [117] MV/RhB UV light 60.6/29.4 2D-CuTCPP [100] RhB Visible light 81.2 Co@NC-600 [118] MB/ RhB NaBH 4 99.9/95.7 nanosheet, of which the TC degradation efficiency can reach 73% within 5 min under visible light. In addition, Zhao's team reported a rapid microwave-assisted hydrothermal route for the assembly of 2D copper-porphyrin MOFs (Cu-TCPP MOFs) within an hour.…”
Section: MVmentioning
confidence: 99%
“…as a precursor to obtain a 2D N-doped carbon-coated cobalt nanoparticle composite (Co@NC). [118] A series experiments showed that when the calcining temperature at 600 °C, the catalyst (2D Co@NC-600) had the best catalytic ability of reducing 4-nitrophenol (4-NP) to 4-aninophenol (4-AP) in the presence of NaBH 4 . 2D Co@NC-600 can reach nearly 100% conversion within 120 s and can maintain stability almost unchanged after five cycles.…”
Section: Industrial Compoundsmentioning
confidence: 99%